Raising Awareness to Transcend Disciplines: Developing Teachers' Critical Awareness Across Disciplines to Increase Indigenous Learner Engagement. Issue 2 (10th November 2014) - Riley, Tasha
<x content-type="archive" xml:space="preserve">Abstract</x> The issue of low graduation rates among Indigenous learners transcends borders. Some argue that racism and discrimination in schools and in wider society impede the success of Indigenous learners. Although teachers may not intend to make discriminatory decisions based on a learner's ascribed characteristics, research has demonstrated that teachers are capable of making biased decisions that deny opportunities to Indigenous learners. After reflecting upon current debates regarding effective educational strategies for diversity and Indigenous learners, the author contends that courses directed towards best practices for Indigenous learners in the classroom may be less beneficial than developing teachers' overall critical consciousness-raising and self-awareness abilities. The author presents what the literature reveals regarding various educational methods, practices, and epistemologies that have been successfully shared across disciplines in order to create more effective teachers and more responsive learners.